Selection of Grasses and Legumes for Pastures of the Arid and Semi-arid Zones. I. Variations of Morphological and Physiological Characters in the Different Strains of Cenchrus setigerus and Selection of a Promising Strain for forage Production - Chakravarty, A. K.; Bhati, G. N. (Indian Forester, 1968)
Variability in morphoiogicai and physiological characters in 10 strains of Cenchrus setigerus Vahl. Was studied under arid conditions at Jodhpur. It was observed that some of the strains can provide useful germplasm to breed desirable forage type for pasture prodution. The strain No. 175 was found to be the most suitable strain for the arid zone, because of its higher yield of forage, highest basal and crown diameters, capacity for maximum tiller production, dark green leaf with longer and broader leaf blades and presistency.